The Impact of Ergonomics on Employees’ Productivity in the Architectural Workplaces - Sinno, Nadine; Ammoun, Mariam; Ferdous Alam, A.S.A. (International Journal of Psychosocial Rehabilitation, 2020)
The office work is a working ecosystem entirely dependent on humans. Office ergonomics focuses on the human well-being and adapts all office components to suit workers’ needs and comfort. The unawareness of the Lebanese designers in particular and the global designers in general on the importance of applying ergonomics programs and implementing well-designed workplaces reached its borders. Therefore, stressing on the significance of ergonomics programs especially in the architectural field is needed to raise the attention for the essentiality of this topic. The major reason for conducting this project is to enhance the awareness on ergonomics importance and its impact on increasing employees’ productivity specifically among Small and Medium Enterprises (SME’s). The study starts with a general literature review shedding the light on the meaning of ergonomics, its types, factors, and how to enhance employee productivity through applying ergonomics. After the theoretical part which revealed an important background to start on investigating the hypothesis of the project the fact findings and conclusions of the project were drawn. Using SPSS program and other tools the research demonstrated and drew the facts in a statistical and graphical way to show clearly the exact outcomes. The data used to emphasize and validate the suggested hypothesis was all collected through questionnaires and interviews at both Block Tech Line sarl and L’artquitecte. Both companies are well-known in the architectural field among small and medium enterprises. The main reason for choosing this kind of enterprises was it expansion in the Lebanese market at first, and it obtained an important a competitive advantage through ergonomics ISO certified programs. The study showed the strong impact of ergonomics on employees’ productivity, and how the absence of one element may influence negatively the employees. The conclusion which is underlining the stated objectives at the beginning of the study, a list of recommendations was suggested on how to enhance implementing ergonomically designed workplaces.